The Effect Of Green Marketing Concept On Consumer Intention To Buy Savana Project Product - Rizky Faizal Alamin; Ike Ratnasari (Universitas Negeri Gorontalo, 2019)
This study aims to determine and analyze the influence part of the green marketing concept where the variables studied include green product, green promotion, green packaging. Towards Savana Project product buying intention, and to know and analyze which variables have the dominant influence on consumer buying interest. The population of this study is all prospective buyers of Savana Project products using the Non-Probability Sampling Method, namely convenience sampling where members of the population can be easily selected as samples. The number of samples in this study were 121 respondents. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis show that all variables simultaneously have a significant effect on buying intention, and are able to contribute to customer loyalty variables by 58.8%. Partially only green products that do not have a significant influence on buying interest. While the other two, namely green promotion and green packaging have a significant influence on consumer buying interest. green promotion becomes the dominant influence variable on customer loyalty with a regression coefficient of 0.501 greater than the other three variables. This shows that green promotion is a variable that greatly influences consumer buying interest.